Camera-Based Mirror Visual Input for Priming Promotes Motor Recovery, Daily Function, and Brain Network Segregation in Subacute Stroke Patients. (April 2019) - Ding, Li; Wang, Xu; Chen, Shugeng; Wang, Hewei; Tian, Jing; Rong, Jifeng; Shao, Peng; Tong, Shanbao; Guo, Xiaoli; Jia, Jie
Background . Camera technique–based mirror visual feedback (MVF) is an optimal interface for mirror therapy. However, its efficiency for stroke rehabilitation and the underlying neural mechanisms remain unclear. Objective . To investigate the possible treatment benefits of camera-based MVF (camMVF) for priming prior to hand function exercise in subacute stroke patients, and to reveal topological reorganization of brain network in response to the intervention. Methods . Twenty subacute stroke patients were assigned randomly to the camMVF group (MG, N = 10) or a conventional group (CG, N = 10). Before, and after 2 and 4 weeks of intervention, the Fugl-Meyer Assessment Upper Limb subscale (FMA_UL), the Functional Independence Measure (FIM), the modified Ashworth Scale (MAS), manual muscle testing (MMT), and the Berg Balance Scale (BBS) were measured. Resting-state electroencephalography (EEG) signals were recorded before and after 4-week intervention. Results . The MG showed more improvements in the FMA_UL, the FMA_WH (wrist and hand), and the FIM than the CG. The clustering coefficient (CC) of the resting EEG network in the alpha band was increased globally in the MG after intervention but not in the CG. Nodal CC analyses revealed that the CC in the MG tended to increase in the ipsilesional occipital and temporal areas, and the bilateral central and parietal areas, suggesting improved local efficiency of communication in the visual, somatosensory, and motor areas. The changes of nodal CC at TP8 and PO8 were significantly positively correlated with the motor recovery. Conclusions . The camMVF-based priming could improve the motor recovery, daily function, and brain network segregation in subacute stroke patients.